2008
DOI: 10.1038/leu.2008.333
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, function and bone marrow trafficking of CD4+CD25+FOXP3+ regulatory T cells in myelodysplastic syndromes (MDS)

Abstract: CD4 þ CD25 þ FOXP3 þ T regulatory cells (T regs ) prevent autoimmunity by restricting overexuberant immune responses, but the same subpopulation can incur detrimental effects on antitumor responses. In both cases, the suppressor potential of T regs appears to be strongly influenced by their compartmentalization. In myelodysplastic syndromes (MDS), immune deregulation and autoimmunity in the early stages might lead to ineffective hematopoiesis and bone marrow (BM) failure, whereas late-stage disease is characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 49 publications
8
95
1
2
Order By: Relevance
“…28,37 It has recently been shown that T-Regulatory cells in early MDS, in contrast to advanced MDS, have a reduced ability to suppress immune responses and, through reduced expression of CXCR4, impaired bone marrow trafficking. 35 In agreement with these findings, we found that chemokine signaling through CXCR4 was deregulated in RA, with CXCR4 being down-regulated in RA by approximately 50% compared with healthy controls in our study. Genes in regular font are expressed at lower levels in À7/del7q compared with healthy controls, whereas genes in bold font are expressed at higher levels in À7/del7q compared with healthy controls.…”
Section: Deregulated Pathways In Myelodysplastic Syndromessupporting
confidence: 81%
See 1 more Smart Citation
“…28,37 It has recently been shown that T-Regulatory cells in early MDS, in contrast to advanced MDS, have a reduced ability to suppress immune responses and, through reduced expression of CXCR4, impaired bone marrow trafficking. 35 In agreement with these findings, we found that chemokine signaling through CXCR4 was deregulated in RA, with CXCR4 being down-regulated in RA by approximately 50% compared with healthy controls in our study. Genes in regular font are expressed at lower levels in À7/del7q compared with healthy controls, whereas genes in bold font are expressed at higher levels in À7/del7q compared with healthy controls.…”
Section: Deregulated Pathways In Myelodysplastic Syndromessupporting
confidence: 81%
“…There is mounting evidence, such as the presence of autoreactive T-cell clones and increased levels of preapoptotic cytokines, suggesting that immune deregulation, especially in early MDS, results in an autoimmune process leading to ineffective hematopoiesis and bone marrow failure, whereas advanced MDS is characterized by the immune evasion and selective growth advantage of the malignant clone. 35,36 In accord with this hypothesis, we have found that among the most significantly deregulated gene pathways in RA are 'immunodeficiency signaling,' 'B-cell receptor signaling,' 'IL4 signaling' and 'chemokine signaling.' The 'primary immunodeficiency signaling' pathway was the most significantly deregulated pathway in RA.…”
Section: Deregulated Pathways In Myelodysplastic Syndromessupporting
confidence: 57%
“…[8][9][10][11] There is also accumulating evidence that impaired function of CD4 ϩ CD25 ϩ regulatory T cells (Tregs) has been implicated in the development of several common autoimmune diseases, 8,10 myelodysplastic syndromes, 12 and AA. 13 Until now, the only report of Treg abnormality in AA has shown that the numbers of circulating Tregs decreased in most patients.…”
Section: Introductionmentioning
confidence: 99%
“…Leukemiainitiating-cells have also been associated with a mast cell signature; the IL2/CD25 axis may serve as a key regulator in leukemic cell activation [36]. As with leukemia, T-reg functionality is distorted in MDS; T-reg receptor profiles as well as migratory and homing capacities to the bone marrow are altered to favor LSC development [37]. Both MDS and leukemia are marked by unique cytokine and chemokine expression patterns [9] and it is likely that this alters the communication landscape between immune cells, stem cells, and stromal cells of the hematopoietic system.…”
Section: Fig 1 a Immune Cells Act As Homeostatic Plasticizers Of Thementioning
confidence: 99%